PENGARUH PERBEDAAN WAKTU PENYAMAKAN NABATI TERHADAP KARAKTERISTIK KULIT TERSAMAK YANG DIHASILKAN - mutiar, Sri; Yusmita, Lisa; Kasim, Anwar (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2023)
Lead time is one of the methods used to eliminate activities that do not add value to a production process. The leather tanning process is generally a very long series of processes with many series of processes of chemicals. The tanning process generally starts with rawhide, hair removal, weak removal, neutralization, pickle, tanning, re-tanning, and finishing. The purpose of this study was to determine the effect of tanning time on the characteristics of leather produced. The material used in this experiment was goat skin. Tanning experiments with various tanning times of 3 hours, 6 hours, 12 hours, and 24 hours. mimosa, quebracho and Acacia mangium bark extract through single tanning. Analysis of leather quality was determined from chemical characteristics of leather, measurement of physical and organoleptic properties of leather. Data analysis used T test to see the effect of time difference. The results showed that to produce tanning of leather that the standard, the tanning time ≥ 12 hours was used.